Comparison of Efficacy of Ciprofloxacin and Co-Trimoxazole in Escherichia Coli Urinary Tract Infection - Muhammad Ayaz; Sayed Ali Zeeshan Kausar; Muhammad Alamgir; Shafiq Muhammad; Fayaz Muhammad Khan; Sami Ullah (Life and Science)
Objective: To compare the efficacy of ciprofloxacin and co-trimoxazole in urinary tract infection due to Escherichia Coli. Study Design: A cross- sectional study. Place and Duration of Study: This study was conducted at the Department of Medicine, Muhammad Teaching Hospital (MTH), Peshawar, Pakistan from 1 July 2022 to 31 December 2022. Methods: Patients were randomly and consecutively assigned to either group by using lottery method (double blind). A total of 194 patients diagnosed with urinary tract infection due to E coli were randomly divided into two groups, 97 patients in each group, using 54% efficacy of ciprofloxacin, 74% efficacy of Co-Trimoxazole, 95% confidence level, and 90% power of test, using WHO software. “Group-A' for Ciprofloxacin 500mg BD and th 'Group-B' for Co-Trimoxazole 960mg BD. All the recruited patients were followed up after the 48 hour of their treatment and results were recorded. The chi-Square test was applied to compare the efficacy results of both drugs where a PValue < 0.05 was considered as significant value. Results: The mean age of group A participants were 48.4 + 11.1 years, whereas, in group B it was 48.2 + 11.5 years. There were 69.1% males and 30.9% females in group A compared to 80.4% males and 19.6% females in group B. After the 48 hour of end treatment, efficacy was 79.3% and 50.5%, in groups A and B respectively (p-value = 0.000). Conclusion: As compared to Cotrimoxazole, Ciprofloxacin is more effective in treating E. coli-caused urinary tract infections.